The effects of colloids or crystalloids on acute respiratory distress syndrome in swine (Sus scrofa) models with severe sepsis: analysis on extravascular lung water, IL-8, and VCAM-1 (Faculty of Medicine Universitas Indonesia, 2016)
Background: Acute respiratory distress syndrome (ARDS) is a fatal complication of severe sepsis. Due to its higher molecular weight, the use of colloids in fluid resuscitation may be associated with fewer cases of ARDS compared to crystalloids. Extravascular lung water (EVLW) elevation and levels of interleukin-8 (IL-8) and vascular cell adhesion molecule-1 (VCAM-1) have been studied as indicators playing a role in the pathogenesis of ARDS. The aim of the study was to determine the effects of colloid or crystalloid on the incidence of ARDS, elevation of EVLW, and levels of IL-8 and VCAM-1, in swine models with severe sepsis.Methods: This was a randomized trial conducted at the Laboratory of Experimental Surgery, School of Veterinary Medicine, IPB, using 22 healthy swine models with a body weight of 8 to 12 kg. Subjects were randomly allocated to receive either colloid or crystalloid fluid resuscitation. After administration of endotoxin, clinical signs of ARDS, EVLW, IL-8, and VCAM-1 were monitored during sepsis, severe sepsis, and one- and three hours after fluid resuscitation. Analysis of data using the Wilcoxon test , Kolmogorov-Smirnov test, Mann-Whitney test, unpaired t test.Results: Mild ARDS was more prevalent in the colloid group, while moderate ARDS was more frequent in the crystalloid group. EVLW elevation was lower in the colloid compared to the crystalloid group. There was no significant difference in IL-8 and VCAM-1 levels between the two groups.Conclusion: The use of colloids in fluid resuscitation does not decrease the probability of ARDS events compared to crystalloids. Compared to crystalloids, colloids are associated with a lower increase in EVLWI, but not with IL-8 or VCAM-1 levels.